Unbecoming a priest: a memoir - Bartlett, Anthony W. (Cascade Books, 2023)
"Tony Bartlett's story is thrillingly upside-down. Rather than the classic conversion narrative of escaping the world to dedicate your life to God, it is about escaping a collapsing institutional order to discover a different self and learning to be in the world. An extraordinary account with pivotal themes of sexuality, trauma, revolution, and relationship, Unbecoming a Priest spans eras, classes, continents, cities, wars, iconic figures, spiritualities, and above all divergent modes of Christian-being-in-the-world. From London to Rome, from Europe to Latin America, journeying with exceptional fellow pilgrims like Mother Teresa, Pedro Casaldaliga, Carlo Carretto, it is a story of pain and messiness becoming ultimately one of joy, life, and meaning. Subtly but surely, the journey is also gospel-inspired, where the figure of Jesus takes on a provocative, anarchic role, helping in the overturning of sacrificial cliches and systems. Inevitably at stake is the meaning of priesthood itself, either propping up an eternal order amidst history's escalating crisis, or seeking with others the germ of authentic new human becoming and hope. Here is the inescapable drama and contemporary truth of unbecoming a priest." --